Conflict in the Perspective of Multicultural Education - Siregar, Izuddinsyah; Pramudita, Pramudita (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
Conflict is an inherent phenomenon in social life and a major challenge in multicultural societies. Differences in values, social status, power, and the unequal distribution of resources often serve as the primary triggers of conflict. This study aims to analyze conflict from the perspective of multicultural education and explore the role of education in mitigating social tensions. Through a theoretical literature-based analysis, this study finds that multicultural education plays a strategic role in fostering social awareness and competencies to create harmony in diverse societies. The key findings of this study indicate that conflict in multicultural societies can be explained through various theoretical perspectives. Marx views conflict as a consequence of class inequalities and the unjust distribution of resources, while Gurr emphasizes that dissatisfaction with structural injustice is a primary factor driving conflict. Meanwhile, Collier"™s greed and grievance theory suggests that conflict arises either from political and economic exploitation by dominant groups or as a reaction to injustices experienced by marginalized groups. In this context, multicultural education based on social justice can serve as a solution to address conflicts by ensuring equal access to education and socio-economic opportunities for all social groups. The implications of this study highlight that multicultural education should not remain a mere normative discourse but should be developed into a systematic and sustainable approach to fostering an inclusive and harmonious society. Multicultural education models such as content-oriented programs, student-oriented programs, and socially-oriented programs are recommended as practical strategies to enhance cross-cultural understanding and strengthen social solidarity. Therefore, multicultural education can play a crucial role in reducing social conflicts and promoting stronger social cohesion in diverse societies.